Personal brand management in the positioning strategy of freelance advertisers - Torres Samaniego, William Giovanny; Alvarado Gaibor, Marla Lovelia; Castro Villacis, Byron Antonio (Scripta Mundi, 2022)
The professional market of advertising communication, public relations and digital marketing presents a growing activity regarding the management of the image and professionals identity, which in advertising terms is called Personal Branding or Marca Personal in Spanish. The Personal Brand also applies to all the professionalsin the different professional fields who give value to their services, enhancing their professional image. The present investigation covers the use of the Personal Brand as a positioning strategy of freelance advertisers, particularly in the city of Guayaquil. It was designed with a mixed approach starting with a non-participatory observation in order to determine from these data a representative sample in the population indicated in previous lines. It was possible to identify the current situation of the use of the personal brand, the tactics applied and the possible implementation models. The findings have been decisive, although somewhat discouraging, since there is a high percentage of freelance advertising professionals who do not apply the previously mentioned strategy in a technically. At the same time, it can be ensured that there is a group interested in claiming its use, since they are aware of its value in the professional field. It was also possible to identify the most useful techniques, means and channels for their purposes.